PENGARUH PEMBERIAN MAKANAN F100 DENGAN BAHAN SUBSTITUSI TEPUNG TEMPE TERHADAP STATUS PROTEIN PASIEN ANAK DENGAN GIZI KURANG - , Diniyah Kholidah, dr. Endy Pardjanto, SpAk., MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Much effort has been made to counter the weaknesses of F100 through the development of substitute food as source of fat/protein with food containing energy and nutrient, high bioavailability and relatively low cost. Objective: To analyze effect of F100 supplementation using substitute tempeh flour on protein status (total protein serum and serum albumin) of undernourished pediatric patients. Method: Experimental research with randomized control clinical trial in 30 undernourished children consisting of open clinical trial in two experiment groups, supplementation of F100 and substitute F100 (isoenergetic and isoprotein diet) within 14 days. The study was undertaken in April-August 2010 at pediatric inpatient room of Dr. Saiful Anwar Hospital Malang. Data of food intake were obtained through visual comstock and 24 hour food recall